Chapter 17: 25 Years of Scaling Up: Nutrition and health interventions in Odisha, India [Nourishing Millions] - Menon, Purnima; Kohli, Neha; van den Bold, Mara; Becker, Elisabeth; Nisbett, Nicholas; Haddad, Lawrence James; Avula, Rasmi (2016)
ODISHA, A STATE of 42 million people in eastern India, is one of the poorest in the country. It has faced many development challenges over the years, including insurgent movements, large pockets of extreme deprivation among scheduled tribe communities, social disparities, and natural disasters, as well as a relatively late fiscal turnaround (in 2004–2005) in comparison with other states. Yet Odisha has made significant progress in reducing child undernutrition—less than India as a whole, but more than many other richer states. How has it achieved this progress?